Next generation sequencing analysis of patients with familial cervical artery dissection - Grond-Ginsbach, Caspar; Brandt, Tobias; Kloss, Manja; Aksay, Suna Su; Lyrer, Philipp; Traenka, Christopher; Erhart, Philipp; Martin, Juan Jose; Altintas, Ayse; Siva, Aksel; de Freitas, Gabriel R; Thie, Andreas; et al. (European stroke journal, 2017)
Background The cause of cervical artery dissection is not well understood. We test the hypothesis that mutations in genes associated with known arterial connective tissue disorders are enriched in patients with familial cervical artery dissection. Patients and methods Patient duos from nine pedigrees with familial cervical artery dissection were analyzed by whole exome sequencing. Single nucleotide variants in a panel of 11 candidate genes (ACTA2, MYH11, FBN1, TGFBR1, TGFBR2, TGFB2, COL3A1, COL4A1, SMAD3, MYLK and SLC2A10) were prioritized according to functionality (stop-loss, nonsense, and missense variants with polyphen-2 score ≥0.95). Variants classified as “benign” or “likely benign” in the ClinVar database were excluded from further analysis. For comparison, non-benign stop-loss, nonsense and missense variants with polyphen-2 score ≥0.95 in the same panel of candidate genes were identified in the European non-Finnish population of the ExAC database (n = 33,370). Results Non-benign Single nucleotide variants in both affected patients were identified in four of the nine cervical artery dissection families (COL3A1; Gly324Ser, FBN1: Arg2554Trp, COL4A1: Pro116Leu, and TGFBR2: Ala292Thr) yielding an allele frequency of 22.2% (4/18). In the comparison group, 1782 variants were present in 33,370 subjects from the ExAC database (allele frequency: 1782/66,740 = 2.7%; p = 0.0008; odds ratio = 14.2; 95% confidence interval = 3.8–52.9). Conclusion Cervical artery dissection families showed enrichment for non-benign variants in genes associated with arterial connective tissue disorders. The observation that findings differed across families indicates genetic heterogeneity of familial cervical artery dissection.